2019
DOI: 10.1016/j.jmbbm.2019.103381
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterisation of human and porcine scalp tissue at dynamic strain rates

Abstract: Several biomedical applications require knowledge of the behaviour of the scalp, including skin grafting, skin expansion and head impact biomechanics. Scalp tissue exhibits a non-linear stress-strain relationship, anisotropy and its mechanical properties depend on strain rate. When modelling the behaviour of the scalp, all these factors should be considered in order to perform realistic simulations. Here, tensile tests at strain rates between 0.005-100 s-1 have been conducted on porcine and human scalp in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 57 publications
(69 reference statements)
1
16
0
Order By: Relevance
“…Nonetheless, our assumption resulted in good correspondence between the model-predicted and the experimentally measured ICP. Finally, we assumed homogeneous properties for the skin and necessarily excluded mechanical properties specific to the face and scalp tissues [67], which can possibly influence the biomechanical responses for offset impacts [68]. Nonetheless, our assumption resulted in good correspondence between the model-predicted and the experimentally measured RD.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Nonetheless, our assumption resulted in good correspondence between the model-predicted and the experimentally measured ICP. Finally, we assumed homogeneous properties for the skin and necessarily excluded mechanical properties specific to the face and scalp tissues [67], which can possibly influence the biomechanical responses for offset impacts [68]. Nonetheless, our assumption resulted in good correspondence between the model-predicted and the experimentally measured RD.…”
Section: Study Limitationsmentioning
confidence: 99%
“…For example, it has been shown that porcine scalp skin tissue has almost twice the elastic modulus and the ultimate tensile strength of its human counterpart. 114 Similarly, mechanical assessment of porcine and human abdominal skin stratum corneum showed significant differences in their Young's moduli. 113 We must also note that pigs are quadrupedal and humans bipedal, as movement and posture can also have significant impact on overall tissue mechanics that may be influential during healing.…”
Section: Further Considerations On Pigs As Models Of Human Skin Healingmentioning
confidence: 99%
“…A set of nodes were selected on the top and bottom, anterior-aspect of the human subject, and defined as a boundary condition with zero translation in three spatial coordinates, but free to rotate in any direction. Each tissue constituent was assigned linear elastic material properties previously reported in the literature [40][41][42][43][44][45][46][47][48][49]: (1) skin (E = 160 MPa; ν = 0.49; ρ = 1020 kg m-3), ( 2…”
Section: Mechanical Modelingmentioning
confidence: 99%